An Intelligent System for Petroleum Well Drilling Cutting Analysis - Marana, Aparecido Nilceu [UNESP]; Chiachia, Giovani [UNESP]; Guilherme, Ivan Rizzo [UNESP]; Papa, João Paulo [UNESP]; Miura, Kazuo; Ferreira, Marystela [UNESP]; Torres, Francisco (Institute of Electrical and Electronics Engineers (IEEE), Computer Soc, 2009)
Cutting analysis is a important and crucial task task to detect and prevent problems during the petroleum well drilling process. Several studies have been developed for drilling inspection, but none of them takes care about analysing the generated cutting at the vibrating shale shakers. Here we proposed a system to analyse the cutting's concentration at the vibrating shale shakers, which can indicate problems during the petroleum well drilling process, such that the collapse of the well borehole walls. Cutting's images are acquired and sent to the data analysis module, which has as the main goal to extract features and to classify frames according to one of three previously classes of cutting's volume. A collection of supervised classifiers were applied in order to allow comparisons about their accuracy and efficiency. We used the Optimum-Path Forest (OPF), Artificial Neural Network using Multi layer Perceptrons (ANN-MLP), Support Vector Machines (SVM) and a Bayesian Classifier (BC) for this task. The first one outperformed all the remaining classifiers. Recall that we are also the first to introduce the OPF classifier in this field of knowledge. Very good results show the robustness of the proposed system, which can be also integrated with other commonly system (Mud-Logging) in order to improve the last one's efficiency.
Keywords: Cutting analysis; petroleum well drilling monitoring; optimum-path forest